Comparison of Cooperative Listening Team and Numbered Head Together Types of Learning Outcomes of Geography in the Material of Earth's Rotation and Revolution - Indri Yuniar Rachmawati; Ha Van Thang; Mike Marcell Zwick (Journal of Social Knowledge Education (JSKE), 2023)
Purpose of the study: This study aims to determine differences in geography learning outcomes using cooperative learning models of listening team types, numbered heads together (NHT) and discussions. Methodology: This study used a Quasi-Experimental research method "Postest-Only Control Design". The population of this study were all students of class X SMA Negeri 1 Colomadu, Karanganyar in the 2016/2017 academic year. Samples were taken by cluster random sampling technique. The selected sample is class X IPS 1, IPS 2 and IPS 3. The technique of collecting data on learning outcomes uses a test technique in the form of essay questions. The data analysis technique used was One Way Variant Analysis (One Way Anava) and post Anava test (Scheffe' method) with a significance level of 5%. Main Findings: The results showed: 1) There were differences in geography learning outcomes using the Listening Team, Numbered Head Together (NHT) cooperative learning model and discussions on the subject matter of Rotational Motion and Earth Revolution for class X students. 2) The Geography learning outcomes using the Listening Team cooperative learning model were better than the Geography learning outcomes using the discussion method. 3) The learning outcomes of Geography using the Numbered Head Together (NHT) cooperative learning model are better than the learning outcomes of Geography using the discussion learning method. Novelty/Originality of this study: Based on the results of previous research, it is known that the cooperative model with the Listening Team and Numbered Head Together (NHT) types can increase student activity and achievement. This is renewable through this research practically learning using cooperative learning models of the Listening Team and Numbered Head Together (NHT) types can improve students' learning outcomes of Geography in the material Rotational Motion and Earth Revolution.